PP20 Is red cell transfusion beneficial and safe after cardiac surgery? Intention-to-treat compared to instrumental variable analyses in the Transfusion Indication Threshold Reduction (TITRe2) randomised controlled trial (RCT). (2nd September 2014) - Pike, K; Rogers, CA; Sterne, JAC; Murphy, GJ; Reeves, BC
Abstract : Background: Perioperative anaemia is strongly associated with adverse outcomes in cardiac surgery patients but, paradoxically, observational analyses find red cell transfusion to be associated with worse clinical outcomes. The TITRe2 RCT tested the hypothesis that a restrictive, compared to liberal, threshold for red cell transfusion would reduce post-operative morbidity and health care costs after cardiac surgery. Methods: This multi-centre RCT recruited patients aged >16 years undergoing non-emergency cardiac surgery with post-operative haemoglobin <9g/dL. Participants were randomised to restrictive or liberal transfusion strategy (transfusion indicated if haemoglobin <7.5g/dL or <9g/dL, respectively). The primary outcome was a serious infectious or ischaemic event in the three months after randomisation. The primary analysis was on an intention-to-treat (ITT) basis using logistic regression. A pre-specified ancillary analysis quantified the dose-response relationship between number of red cell units transfused and the risk of morbidity and mortality, stratified by trial arm. Two primary statistical methods for handling confounding were applied in the ancillary analysis: conventional adjustment for covariates (CA); and an instrumental variable (IV) analysis estimating the effect of transfusion in the patients treated in the trial, with randomised allocation as the instrument. Results: The analysis population consisted of 1000 patients in the restrictive group and 1003 in the liberal group. Transfusion rates (≥1 red cell unit) after randomisation were 53.4% and 92.2% in the restrictive and liberal groups, respectively. The primary outcome occurred in 35.1% (331/944) and 33.0% (317/962) of participants, with the primary ITT analysis slightly favouring the liberal threshold (odds ratio (OR) 1.11, 95% CI 0.91–1.34, p = 0.30). Nevertheless, the CA analysis estimated that the odds of the primary outcome increased with increasing red cell units transfused (OR per unit 1.30, 95% CI 1.24–1.37, p < 0.001). The corresponding group-specific ORs were 1.27 (95% CI 1.18–1.36) in the restrictive group and 1.35 (95% CI 1.25–1.45) in the liberal group. By contrast, a provisional simple IV analysis (any versus no red cell transfused) appeared to suggest no increased risk from transfusion (relative risk 0.74, 95% CI 0.35–1.56, p = 0.43). Further IV analyses to quantify the dose relationship are ongoing. Discussion: This RCT was designed as a superiority trial but the primary analysis has found a non-inferiority answer that contradicts previous observational analyses and RCTs of restrictive versus liberal thresholds in other surgical specialties. The IV analysis should help us to understand the true effect of red cell transfusion in a cardiac surgery population. Acknowledgements: The trial was funded by the United Kingdom National Institute for Health Research (NIHR) Health Technology Assessment program (ref: 06/402/94). The views and opinions expressed are those of the authors and do not necessarily reflect those of the HTA program, NIHR, the UK NHS or the Department of Health.